Does privatization raise productivity? Evidence from comprehensive panel data on manufacturing firms in Hungary, Romania, Russia, and Ukraine - J. David Brown; John S. Earle; Almos Telegdy (W.E. Upjohn Institute for Employment Research, 2004)
We analyze the impact of privatization on multifactor productivity (MFP) using long panel data for nearly the universe of initially stateowned manufacturing firms in four economies. Controlling for firm and industry-year fixed effects and employing a wide variety of measurement approaches, we estimate that majority privatization raises MFP about 28% in Romania, 22% in Hungary, and 3% in Ukraine, with some variation across specifications, while in Russia it lowers it about 4%. Privatization to foreign rather than domestic investors has a larger impact (about 44%) and is much more consistent across countries. The positive effects emerge within a year in Hungary, Romania, and Ukraine and continue to grow thereafter, but are still ambiguous even after 5 years in Russia. Pre-privatization MFP exceeds that of firms remaining state-owned in all countries, implying that cross-sectional estimates overstate privatization effects. The patterns of the estimated effects cast doubt on a number of explanations for when privatization works.
Keywords: D24; G34; L33; P31; 330; privatization; productivity; foreign ownership; Hungary; Romania; Russia; Ukraine; transition; Produktivität; Privatisierung; Verarbeitendes Gewerbe; Vergleich; Ungarn; Rumänien; Russland; Ukraine